WHY DO TURKISH POLICE OFFICERS COMMIT SUICIDES? ANALYSIS OF SUICIDE CASES BETWEEN 2001 AND 2012 - Harmancı, Fatih Mehmet; Mus, Ekrem; Tosun, Hamza; Tascı, Ufuk (European Scientific Journal, ESJ, 2015)
The concept of suicide existed since the beginning of human history, Anomie, sudden changes on living conditions, lack of communication between individuals are some fundamental causes of suicide. This study focuses on examining the Turkish police suicide cases, solutions to suicides, risks associated with groups, suicide-related factors, suicidal motivation, police suicide symptoms, crisis situation. Suicidal behavior is described as a serious problem all over the world. Suicidal behavior requires a multi-dimensional approach including biological, psychological and social factors are taken into consideration. The researchers analyse the frequency of suicide attempts, format, preparing and triggering factors, clinical presentation, psychiatric disorders, biological factors, socio-demographic features throught the world. In this study, two secondary data was used; the first one is the official data held by the Security General Directorate of Statistics for police suicides and the second data is provided the Turkish Statistical Institute (TSI) on suicides cases in Turkish society. The analysis of two data, protective elements of conceptual framework is discussed in the article. The findings, results and recommendations are discoursed at the end of the paper.